2012
DOI: 10.1177/1065912912470759
|View full text |Cite
|
Sign up to set email alerts
|

Secular-Islamist Cleavage, Values, and Support for Democracy and Shari’a in the Arab World

Abstract: Public opinion polls demonstrate that Arab citizens support both democracy and shari’a. I argue that individual values related to the secular-Islamist cleavage are instrumental in explaining this joint support. The analysis of the Arab Barometer Survey shows that individuals holding Islamic values are more favorable of shari’a, whereas those with secularist values tend to support democracy. However, the bivariate probit estimations also confirm that Arab opinion about these governing principles is more complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 30 publications
4
46
0
Order By: Relevance
“…The answers are given from a scale from 1 to 4 and were recoded such as "Absolutely inappropriate = 1" and "Very appropriate = 4". As such, this variable differentiates weak from ardent supporters of Shari'a (Ciftci 2012).…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations
“…The answers are given from a scale from 1 to 4 and were recoded such as "Absolutely inappropriate = 1" and "Very appropriate = 4". As such, this variable differentiates weak from ardent supporters of Shari'a (Ciftci 2012).…”
Section: Datamentioning
confidence: 99%
“…Following Ciftci (2012), in this paper we have also studied how particularism affects support for Shari'a, another side of support for democracy in the Arab world. Our summary statistics show that several supporters of democracy also favor Shari'a in the Arab world.…”
Section: Support For Democracy and Support For Shari'amentioning
confidence: 99%
See 2 more Smart Citations
“…Polling data from the Arab Barometer Surveys found that, across seven different Arab countries, 34% of respondents said they preferred Sharia without democracy, and 41% said they supported both. Only a small minority (14%) said they supported democracy without Sharia (Ciftci 2012). 6 The role of Islam is growing significantly in countries where it was once thought to be weakening, such as in Turkey and Tunisia (see Hirschl 2011).…”
Section: Conversely Shadi Hamid (2016) Writes In His Book Islamic Exmentioning
confidence: 99%